2017
DOI: 10.1016/j.dci.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification, annotation and expression analysis of 29 Rho GTPase genes from channel catfish (Ictalurus punctatus) after bacterial infections

Abstract: The Rho family GTPases are a group of small monomeric G proteins, which are molecular switches in signaling pathways. They have been known to regulate a diverse range of cellular processes including actin cytoskeleton rearrangement and microtubule dynamics. In particular, their participations in immune responses are also significant. However, little information of the Rho GTPases is available in teleost including channel catfish, an economically important species and one of the best teleost models forimmunolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Many gene families were induced after E. ictaluri infection, including heat shock proteins (Song et al, 2014, 2016; Xie et al, 2015), interlekin 17 (Wang X. et al, 2014), l-rhamnose-binding lectins (Thongda et al, 2014), nitric oxide synthase genes (Yao et al, 2014), claudins (Sun et al, 2015), peptidoglycan recognition proteins (Sun et al, 2014), Rab GTPases (Wang R. et al, 2014), Rho GTPase (Tan et al, 2017), suppressors of cytokine signaling genes (Yao et al, 2015), cytochrome P450 genes (Zhang et al, 2014), serpins (Li et al, 2015), bcl-2 genes (Yuan et al, 2016), cathepsins (Geng et al, 2015; Wang et al, 2015; Dong et al, 2016), tumor suppressor genes (Mu et al, 2015), complement regulatory protein genes (Jiang et al, 2015), septins (Fu et al, 2016), chemokines (Fu et al, 2017a,b,c), galectins (Zhou et al, 2016), apolipoproteins (Yang et al, 2017), receptor tyrosine kinases (Tian et al, 2015), NF-kB related genes (Wang et al, 2017c), phosphoinositide-3-kinases (Li et al, 2016), NCK and ABI adaptor genes (Zhou et al, 2017a), JAK and STAT genes (Jin et al, 2018). These studies indicated that most of the immune related genes were involved in the E. ictaluri disease responses.…”
Section: Part I: Enteric Septicemia Of Catfish (Esc)mentioning
confidence: 99%
“…Many gene families were induced after E. ictaluri infection, including heat shock proteins (Song et al, 2014, 2016; Xie et al, 2015), interlekin 17 (Wang X. et al, 2014), l-rhamnose-binding lectins (Thongda et al, 2014), nitric oxide synthase genes (Yao et al, 2014), claudins (Sun et al, 2015), peptidoglycan recognition proteins (Sun et al, 2014), Rab GTPases (Wang R. et al, 2014), Rho GTPase (Tan et al, 2017), suppressors of cytokine signaling genes (Yao et al, 2015), cytochrome P450 genes (Zhang et al, 2014), serpins (Li et al, 2015), bcl-2 genes (Yuan et al, 2016), cathepsins (Geng et al, 2015; Wang et al, 2015; Dong et al, 2016), tumor suppressor genes (Mu et al, 2015), complement regulatory protein genes (Jiang et al, 2015), septins (Fu et al, 2016), chemokines (Fu et al, 2017a,b,c), galectins (Zhou et al, 2016), apolipoproteins (Yang et al, 2017), receptor tyrosine kinases (Tian et al, 2015), NF-kB related genes (Wang et al, 2017c), phosphoinositide-3-kinases (Li et al, 2016), NCK and ABI adaptor genes (Zhou et al, 2017a), JAK and STAT genes (Jin et al, 2018). These studies indicated that most of the immune related genes were involved in the E. ictaluri disease responses.…”
Section: Part I: Enteric Septicemia Of Catfish (Esc)mentioning
confidence: 99%
“…Columnaris disease, caused by Flavobacterium columnare, is one of the most frequently occurring disease of catfish (Shoemaker et al, 2008;Zhao et al, 2015). To understand the immune responses after bacterial infection, a large number of studies have been conducted with immune related genes in catfish, including pathogen recognition receptors (Rajendran et al 2012a;2012b;Zhang et al, 2013;Sun et al, 2014), claudins (Sun et al, 2015), serpins (Li et al, 2015), chemokines (Bao et al, 2006;Peatman et al, 2006;Fu et al, 2017), complementary proteins (Jiang et al, 2015), tumor suppressor proteins (Mu et al, 2015), Rho GTPase genes (Tan et al, 2017), apolipoprotein genes (Yang et al, 2017), and a number of regulatory and response genes involved in disease responses (Yao et al, 2014;Yuan et al, 2016). Suppression of NF-κB pathway was reported in catfish gill tissue after columnaris infection (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression fold-change was determined based on the normalized RPKM using a proportions-based Kal's test. The SHSP, HSP60/10 and HSP90 genes with p < 0.05, absolute fold change value >2 and total reads number >5 were regarded as the differentially expressed genes(Tan et al, 2017;Zhou et al, 2017). total of 10 SHSP genes were identified in sea cucumber in-The two HSP60/10 genes, AjHSP10 and AjHSP60, were identified.…”
mentioning
confidence: 99%